Boundary between reality and fiction: analysing socio-political influences of a criminal mind in the film, Joker (2019) - Anisha, Afsana Anjum (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2021.